Menelaah Keberpihakan Media dalam Melaporkan Hasil Pilpres 2024 - Al Utama, Lazuardy; Yoedtadi, Moehammad Gafar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This study aims to analyze the framing objectivity of the news coverage of the 2024 Presidential Election results on two leading online media platforms in Indonesia, namely Kompas.com and Mediaindonesia.com. This research uses a qualitative framing analysis method with the Zhongdang Pan and Gerald M. Kosicki model to provide an overview of the objectivity of the news coverage by these two media outlets in reporting the announcement of the 2024 Presidential Election results, as well as to identify potential biases and partisanship that may arise in the reporting. The topics discussed in this journal include the framing analysis of the news coverage of the 2024 Presidential Election results on Kompas.com and Mediaindonesia.com, identification of potential biases and partisanship in the reporting, and a discussion on the objectivity of the media in covering political events. The conclusions and recommendations generated are expected to contribute to the knowledge of news framing and media objectivity in the context of the Presidential Election. This research is expected to promote more objective and transparent journalistic practices and help readers become more critical in evaluating the information presented by the mass media. Penelitian ini bertujuan untuk menganalisis framing objektivitas pemberitaan pengumuman hasil Pemilihan Presiden (Pilpres) 2024 pada dua media online terkemuka di Indonesia, yaitu Kompas.com dan MediaIndonesia.com. Penelitian ini menggunakan metode analisis framing kualitatif dengan model Zhongdang Pan dan Gerald M. Kosicki untuk memberikan gambaran mengenai objektivitas pemberitaan kedua media tersebut dalam meliput pengumuman hasil Pilpres 2024, serta mengidentifikasi potensi bias dan keberpihakan yang mungkin muncul dalam pemberitaan. Topik yang akan dibahas dalam jurnal ini meliputi analisis framing pemberitaan pengumuman hasil Pilpres 2024 pada Kompas.com dan MediaIndonesia.com, identifikasi potensi bias dan keberpihakan dalam pemberitaan, serta diskusi mengenai objektivitas media dalam meliput peristiwa politik. Kesimpulan dan saran yang dihasilkan diharapkan dapat memberikan kontribusi pada pengetahuan tentang framing berita dan objektivitas media dalam konteks Pilpres. Penelitian ini diharapkan dapat mendorong praktik jurnalistik yang lebih objektif dan transparan, serta membantu pembaca untuk lebih kritis dalam mengevaluasi informasi yang disajikan oleh media massa.